A mutation in polynucleotide phosphorylase from Escherichia coli impairing RNA binding and degradosome stability - Regonesi, Maria Elena (Oxford University Press, 2004)
Polynucleotide phosphorylase (PNPase), a 3′ to 5′ exonuclease encoded by pnp, plays a key role in Escherichia coli RNA decay. The enzyme, made of three identical 711 amino acid subunits, may also be assembled in the RNA degradosome, a heteromultimeric complex involved in RNA degradation. PNPase autogenously regulates its expression by promoting the decay of pnp mRNA, supposedly by binding at the 5′-untranslated leader region of an RNase III-processed form of this transcript. The KH and S1 RNA-binding domains at the C-terminus of the protein (amino acids 552–711) are thought to be involved in pnp mRNA recognition. Here we show that a G454D substitution in E.coli PNPase impairs autogenous regulation whereas it does not affect the catalytic activities of the enzyme. Although the mutation maps outside of the KH and S1 RNA-binding domains, analysis of the mutant protein revealed a defective RNA binding, thus suggesting that other determinants may be involved in PNPase–RNA interactions. The mutation also caused a looser association with the degradosome and an abnormal electrophoretic mobility in native gels. The latter feature suggests an altered structural conformation of PNPase, which may account for the properties of the mutant protein.